The 5C model: Clinical approach to peripheral neuropathy - Sanjay Kalra; Atul Dhingra; Suneet Kumar Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Peripheral neuropathy is a common condition which is often missed in primary care. The 5C model simplifies the clinical approach to peripheral neuropathy, listing steps of history taking, physical examination and investigations. One begins by eliciting complaints and concerns, and “classifying by the calendar”. Comorbid and contributory diseases, concomitant medications and contacted toxins, are then identified. The complications of neuropathy, and the corrective measures undertaken so far, are explored. This is followed by a physical examination, and supplemented by investigations. Once the diagnosis is confirmed, comprehensive management, guided by the LEMON mnemonic, which lists the various facets of neuropathy care, has to be planned. KEYWORDS: Diabetes, nerve care, neuropathy, nutrition, person centred care, primary care.